Girinos de espécies do gênero Ololygon pertencentes ao grupo "Catharinae" no Estado do Rio de Janeiro (Amphibia, Anura, Hylidae) - Carvalho-e-Silva, Sergio Potsch de (1986)
The study of morphology and habits of tadpoles and of the reprodutive behaviour of six species of the “catharinae” group of the genus Ololygon in the State of Rio de Janeiro, viz: albicans, argyneornata, flavoguttata, humilis, obtriangulata and trapicheiroi demonstrated that they are all full species. Four subgroups are identified: “argyreornata”, including argyneornata and humilis, “trapicheiroi” including albicans trapicheiroi, “flavoguttata” including only flavoguttata, and “obtriangulata”. Some aspects of morphology, such as the size of the nostrils and of the spiracle opening as well as the number of labial papilae are confronted with the features of the water in which the tadpoles live, respectively. All the tadpoles studied here live in the bottom of clear and cool water, inside the forests or in their border.